Liquidus Projection of the Ni-Sc-Zr System - Jiang, Shuwen; Tang, Wenjian; Wang, Yao; Huang, Dandan (Journal of phase equilibria and diffusion, 2022)
In this work, the liquidus projection of the Ni-Sc-Zr ternary system has been experimentally investigated using forty-three as-cast alloys for the first time. The determination of primary phase regions, solidification paths and invariant reaction temperatures has been made based on microstructural characterization via scanning electron microscopy (SEM) with energy-dispersive spectrometer (EDS) and Differential Scanning Calorimeter (DSC). In the constructed liquidus projection, up to fifteen primary solidification phases, including BCC_A2, HCP_A3, Sc 2 Ni, NiZr 2 , BCC_B2, NiZr, Ni 10 Zr 7 , Ni 21 Zr 8 , Ni 11 Zr 9 , ScNi 2 , Ni 7 Zr 2 , Sc 2 Ni 7 , ScNi 5 , Ni 5 Zr and FCC_A1, were observed. Among these the ordered BCC_B2 phase forms the dominant primary solidification field while the Sc 2 Ni and HCP_A3 phase regions are described to expand deeply into the ternary system. In addition, a ternary eutectic reaction and seven ternary transition reactions are proposed as invariant reactions.